Analisis Kesiapan Penerapan Rekam Medis Elektronik Menggunakan Standar CCERA Pada Rumah Sakit Umum Denpasar Bali - Pradnyantara, I Gusti Agung Ngurah Putra; Faidah, Nurul (Akademi Perekam dan Informasi Kesehatan Imelda, 2025)
Based on PMK number 24 of 2022, all health service facilities must provide electronic medical records in accordance with the Minister's regulations. No later than 31 December 2023. To make this policy a success, it is important to assess the needs and readiness of health service facilities to help the successful implementation of RME. Readiness assessments prior to implementing an information system can be used to determine readiness, indications and requirements in facilitating EMR implementation. The purpose of this study is to assess the readiness of implementing electronic medical records in terms of organization, management, operations and IT. This research is a qualitative descriptive research with a case study plan, taking place at RSU Dharma Yadnya Depasar. The data collected was readiness to implement EMR as seen from organizational alignment and management capacity, by conducting in-depth interviews. Research subjects were determined using purposive sampling who were deemed to have the capacity to make decisions regarding RME. Hospitals are said to be ready to implement electronic medical records which will be applied to inpatient units, this can be seen from organizational alignment, management capacity, operational capacity and technical capacity where culture, organization, leadership, strategy, information management, clinical staff, accountability and finance The budget has been planned and has begun to be implemented.